2015
DOI: 10.1111/aas.12563
|View full text |Cite
|
Sign up to set email alerts
|

High PEEP levels are associated with overdistension and tidal recruitment/derecruitment in ARDS patients

Abstract: In this series of patients with ARDS of mainly pulmonary origin, application of high levels of PEEP did not decrease tidal recruitment/derecruitment, but instead consistently increased tidal and maximal hyperinflation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
0
19
0
2
Order By: Relevance
“…PEEP-induced EELV normalization is not necessarily lung protective by itself. A forced PEEP raise may lead to injurious hyperinflation of the persisting healthy lung tissue even without achieving a fully recruited lung [28]. In our model sustained hyperinflation is unlikely due to only minimal occurrence of high V A /Q ratios going along with decent changes of tidal ventilation in the non-dependent lung areas.…”
Section: Discussionmentioning
confidence: 97%
“…PEEP-induced EELV normalization is not necessarily lung protective by itself. A forced PEEP raise may lead to injurious hyperinflation of the persisting healthy lung tissue even without achieving a fully recruited lung [28]. In our model sustained hyperinflation is unlikely due to only minimal occurrence of high V A /Q ratios going along with decent changes of tidal ventilation in the non-dependent lung areas.…”
Section: Discussionmentioning
confidence: 97%
“…Results from preclinical studies using animals [4, 5] and studies in humans [6, 7] support the use of positive end-expiratory pressure (PEEP), to prevent or at least minimize atelectrauma. PEEP, however, can also lead to lung injury due to overdistension [8, 9], so-called volutrauma [1]. …”
Section: Introductionmentioning
confidence: 99%
“…The importance of PEEP application for maintaining adequate gas exchange while preventing ventilator-induced lung injury is especially emphasized (7,10,22,23). Many studies suggested that PEEP and the alveolar recruitment maneuver application improved ventilation-perfusion and gas exchange (7,24,25).…”
Section: Discussionmentioning
confidence: 99%